2012 IEEE International Conference on Power Electronics, Drives and Energy Systems (PEDES) 2012
DOI: 10.1109/pedes.2012.6484409
|View full text |Cite
|
Sign up to set email alerts
|

Deriving inertial response from a non-inertial PV system for frequency regulation

Abstract: As photovoltaic (PV) penetration is gaining its momentum in the recent past, grid codes will demand contribution by PV systems to frequency regulation. This paper presents an investigation into the frequency regulation aspect of photovoltaic systems. An inertial response from photovoltaic system is derived by making it to work away from MPPT point of operation. The case of frequency response under deloaded operation with frequency regulation is compared with the case when the photovoltaics are not contributing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 16 publications
0
24
0
Order By: Relevance
“…RES are capable of providing synthetic inertia, too [5,6,29,37]. Future research will indicate whether these sources are capable of providing synthetic inertia at lower costs then the evaluated storage systems in this work.…”
Section: Conclusion and Future Researchmentioning
confidence: 89%
“…RES are capable of providing synthetic inertia, too [5,6,29,37]. Future research will indicate whether these sources are capable of providing synthetic inertia at lower costs then the evaluated storage systems in this work.…”
Section: Conclusion and Future Researchmentioning
confidence: 89%
“… PV-PPs usually operate by maximizing the power production, meaning that no power reserves are maintained for frequency control [3][4][5][6].  Unlike conventional synchronous generators, PV units have no rotating parts; as a result, no inertial response can be provided during major power disturbances [2,3,7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, most works examine transient and small signal stability [8][9][10]14,15], without considering the effects of PV-PP penetration on frequency stability. Only a small number of studies are found in which the inertial response capability of deloaded PV units is directly addressed [4][5][6]. Nevertheless, these studies investigate the control strategy itself without considering the problem from a power system perspective.…”
Section: Introductionmentioning
confidence: 99%
“…In general, PV power plants operate at the maximum power point tracking mode according to certain meteorological conditions (i.e., temperature T and irradiation G), maximizing the revenues from selling energy [121]. Contributions focused on this technique can be found in [122,123,124,125,126,127]. By curtailment, we are operating the PV plant at a de-loaded point P del , below P M P P , so that the PV plants are able to support system frequency, as some power reserves ∆P = P M P P − P del are available.…”
Section: Pv Power Plant Frequency Control Strategiesmentioning
confidence: 99%